SISTEM INFORMASI PENGAJUAN PERUBAHAN DATA MAHASISWA PADA UNIVERSITAS DEHASEN BENGKULU BERBASIS ONLINE - Novisyah Novisyah; Khairil Khairil; Ricky Zulfiandry; Indra Kanedi (JUTIM (Jurnal Teknik Informatika Musirawas), 2026)
This initial registration will serve as important preliminary information, which becomes urgent when the student in question needs to fulfill certain requirements while the data at Universitas Dehasen Bengkulu does not match their previous identity. Thus, data discrepancies resulting from inconsistencies with previous identities may lead to distrust in the accuracy of existing data. This could negatively impact job searches due to formal data inconsistencies, raising suspicions of fraudulent data. Therefore, a system providing Student Data Change (PDM) services is needed as a means to correct student data. The system implementation uses PHP programming language with MySQL database, and the method employed in this study is Waterfall method. Waterfall method enables the analysis of system requirements to identify weaknesses in the old system, followed by the design of the new system and its subsequent development. The conclusion of this research indicates that the website-based student data change request information system has been successfully implemented and provides optimal services for both students and academic management.